Pendulum with aerodynamic and viscous damping - Soraya, Herlin (Journal of Applied Information, Communication and Technology, 2016)
In this paper we discuss about how the relationship between non-linear differential equations on aerodynamic damping with linearly viscous damping equations. And it turns out after analyzing that the changes that occur pendulum that changes from the start of the maximum state to a stable state takes time so that changes that occur until the state is stable, this change can be reduced with the use of viscous damper